2008
DOI: 10.1213/ane.0b013e31816d14f3
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of a Dynamic Model to Account for the Progress of Labor in the Assessment of Pain

Abstract: We have developed and validated a model for describing pain over the course of labor. Our model is suited to the statistical analysis of covariance and could potentially be used to compare the effects of covariants on labor pain and the rate of change of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Despite methodological variations in relation to the sample and details that distinguish the study design, in one research, great variation in pain intensity was shown by scores 0 to 10 during the contractions throughout the evolution of labor (26) . …”
Section: Statisticalmentioning
confidence: 99%
“…Despite methodological variations in relation to the sample and details that distinguish the study design, in one research, great variation in pain intensity was shown by scores 0 to 10 during the contractions throughout the evolution of labor (26) . …”
Section: Statisticalmentioning
confidence: 99%
“…Based on the earlier studies, [1][2][3][4][5] we hypothesized significant heterogeneity among hospitals in the duration of labor analgesia for vaginal delivery.…”
Section: Large Heterogeneity In Mean Durations Of Labor Analgesia Amomentioning
confidence: 99%
“…5 Parturients who wish to have a more natural, less painful, labor experience may reject active management of labor. 4 Although the AQI currently lacks both patient factor data and relevant data on obstetric management, American Society of Anesthesiologists and American College of Obstetricians and Gynecologists have recently announced the Maternal Quality improvement Project to address this deficiency. l CONCLUSIONS Using data from the American Society of Anesthesiologists' AQI, we showed that the mean durations of labor analgesia for vaginal delivery have large heterogeneity among US hospitals.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently this analytic technique was applied to build a sigmoidal mathematical model of labor pain. 18 A retrospective cohort study used data from 500 laboring women who ultimately delivered vaginally to derive a biexponential equation to describe cervical dilation over time, 19 and to show that patient weight, neuraxial analgesia, and Asian race each influence the progress of labor independently. Substantial individual variability was noted in both the labor pain and labor progress models.…”
Section: Communicationmentioning
confidence: 99%